Will the new stability and growth pact succeed? : an economic and political perspective - Buti, Marco; European Commission : Directorate-General for Economic and Financial Affairs (Brussels- Belgium: European Comission: Directorate-General for Economic and Financial Affairs, 2006)
While the Maastricht Treaty establishes the entry conditions for Member States to join the single currency, the Stability and Growth Pact (SGP) aims to make budgetary discipline a permanent feature of EMU. Consequently, the Pact is commonly interpreted as a major building block of EMU's architecture: the SGP 'must rank as one of the most remarkable pieces of policy coordination in world history. The purpose of this paper is to offer an initial evaluation of the SGP reform. Section Two reviews the main fiscal policy developments in the early years of EMU which were at the basis of the crisis of the SGP 'mark I'. Section Three describes the reformed SGP and an assessment of its main features. Section Four presents some reflections on the political economy of the EU rules, comparing the new SGP with the Maastricht Treaty and the SGP 'mark I'. The final section concludes.
Economic Papers